How do exhausted parents experience their interactions with their children? A qualitative and participative study - Dubois, Anne-Catherine; Roberti-Lintermans, Margaux; Mallien, Zoé; François, Aurore; Lahaye, Magali; De Mol, Jan; Aujoulat, Isabelle (Frontiers in Public Health, 2024)
Parental burnout, known as a state of physical and psychological exhaustion, results in an imbalance between the parent's perceived stressors in relation to parenting, and the resources available to the parent to cope with such stressors. The causes and consequences of parental burnout for the parents themselves have been studied from the parents' point of view, but the perception of parents regarding the impact of parental burnout on the parent-child relationship has not yet been documented. We conducted a qualitative study through semi-structured interviews with exhausted parents (n=21). We aimed to better understand their general interactions with their children, as well as the way they communicate with them about their state of exhaustion, knowing that dealing with parental suffering can have a long-term impact on the child. Our results reveal that exhausted parents experience a widespread loss of control in all areas of their lives, particularly in their interaction with their children, which generates feelings of guilt and shame. Communicating their experience to their children can create various difficulties for both parents and children. This may complicate the process of seeking help and reinforce the feeling of isolation. An emerging result from our analysis leads us to identify a a supprimé: legitimacy6 2 This is a provisional file, not the final typeset article need to be heard and validated in their suffering among the exhausted parents who took part in this research.